Source-Specific Patterns of Marine Debris and Associated Ecological Impacts in the Red River Estuary of Xuan Thuy National Park, Vietnam - Giles, Rachel K.; Nguyen, Cindy Anh Thu; Hồ, Thu Thi Yến; Nguyến, Công Văn; Ngô, Ngoc Thi; Rochman, Chelsea M. (Frontiers in Environmental Science, 2021)
Vietnamese rivers are among the top ten contributors of anthropogenic debris to the ocean. However, there is limited empirical research documenting debris and its effects in Northern Vietnam. The goal of our research was to conduct the first baseline assessment of anthropogenic debris in the Red River. We aimed to understand the sources, accumulation patterns, and ecological effects of anthropogenic debris in the Red River (Song Hong) estuary. To assess debris patterns, we conducted standing stock debris surveys at sites in the mouth, and upstream of the Red River. To assess the ecological effects of anthropogenic debris on mangrove ecosystems, we measured mangrove diameter, canopy cover, and number of crab burrows/m2 in the same debris transects. Anthropogenic debris was found at all sites, and plastic was the most common material. We identified a non-significant trend, whereby ecological indices declined with increasing amounts of debris. Overall, our results demonstrate that anthropogenic debris is ubiquitous in the Red River estuary, composition varies among sites, and this debris may have adverse or neutral ecological effects on mangrove ecosystem health. Future work should conduct debris assessments at larger spatial scales, and assess ecological responses at the community or population level over extended time periods.